O RETORNO SOBRE O INVESTIMENTO (ROI) DA SUSTENTABILIDADE NO SETOR DE FRANQUIAS DE ALIMENTAÇÃO - Chaves, Flávio Gomes (2013)
ABSTRACT Scientific advances continue to reveal environmental risks and at the same time, the understanding of the restaurant industry on sustainability also evolves, as well as best practices and government regulations. Consumer understanding on the topic evolves also influencing their purchase decisions. In this context, many companies begin to engage in efforts to expand the sustainability of its operations, but there is ignorance and uncertainty about the return on their investments in this area. For an industry that operates on low profit margins, sustainable practices can be perceived as a high cost of implementation, becoming an impediment in the adoption of socially responsible management methodology. Several philanthropic experiments have already being successful, but it is necessary to advance the on promotion of sustainable development practices. In this scenario, this paper will discuss the current scenario of sustainability and social responsibility in the food franchise sector, establish metrics to measure return on investment (ROI) and will propose a methodology that incorporates the concept of sustainability into business strategy of companies. The aim is to show that the suggested model of a management system focused on sustainability proves profitable since the profit outlook is a powerful way to engage the private sector that needs a return on investment to mobilize resources. Based on the theory and practice analysis, aims to promote awareness of the industry to adopt this methodology.